2017
DOI: 10.1523/jneurosci.3900-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential Aging Trajectories of Modulation of Activation to Cognitive Challenge in APOE ε4 Groups: Reduced Modulation Predicts Poorer Cognitive Performance

Abstract: The present study was designed to investigate the effect of a genetic risk factor for Alzheimer's disease (AD), ApolipoproteinE 4 (APOE4), on the ability of the brain to modulate activation in response to cognitive challenge in a lifespan sample of healthy human adults. A community-based sample of 181 cognitively intact, healthy adults were recruited from the Dallas-Fort Worth metroplex. Thirty-one APOE4ϩ individuals (48% women), derived from the parent sample, were matched based on sex, age, and years of educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…We then matched these 15 APOE ε4+ individuals (ε4/ε4: n = 2; ε2/ε4: n = 3; ε3/ε4: n = 10) with 15 individuals who were APOE ε4- (ε2/ε3: n = 2; ε2/ε3: n = 3; ε3/ε3: n = 10) based on age and years of education. Similar to the methodology of Foster et al (2017), we retained all ε4+ heterozygotes, including ε2/ε4 individuals, as any individual with an ε4 allele is at greater risk of AD than individuals without ε4 alleles (Liu et al, 2013). Therefore, the current study included 30 healthy adults, aged 60 to 90 years, with an average age of 69 years (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…We then matched these 15 APOE ε4+ individuals (ε4/ε4: n = 2; ε2/ε4: n = 3; ε3/ε4: n = 10) with 15 individuals who were APOE ε4- (ε2/ε3: n = 2; ε2/ε3: n = 3; ε3/ε3: n = 10) based on age and years of education. Similar to the methodology of Foster et al (2017), we retained all ε4+ heterozygotes, including ε2/ε4 individuals, as any individual with an ε4 allele is at greater risk of AD than individuals without ε4 alleles (Liu et al, 2013). Therefore, the current study included 30 healthy adults, aged 60 to 90 years, with an average age of 69 years (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…With the help of BrainAGE, we were able to better stratify these findings by revealing a further association of IFG recruitment with BrainAGE: Not only do APOE ε4 carriers show a need for compensation, but especially do APOE ε4 carriers with older-appearing brains, i.e., individuals with maximal pathological burden. Recent work suggests that APOE ε4 is associated with a different lifespan trajectory regarding the modulation of brain activation under cognitive load (Foster et al, 2017 ). This corroborates our findings of APOE variant as a strong moderator with high impact on neuronal recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of the ε4 allele are not only at an increased risk of AD but also are prone to early onset.2 Additionally, the probability of remaining unaffected over time will also decrease in an apoE4 gene dose-dependent manner.3 However, the prevalence of APOE ε4 among people with AD varies across geographic regions and is significantly lower in Asia than in North America and Europe.4 It has been demonstrated that APOE ε4 contributes to the biological modulation of β-amyloid (Aβ) clearance.5 Genome-wide association studies (GWASs) evaluating the cerebral amyloid burden endophenotype have also reinforced APOE ε4’s role in amyloid accumulation.6 And previous longitudinal studies find that there is only a marginal joint effect of AD genes (such as CLU, PICALM, BIN1, CR1, ABCA7, MS4A6A, MS4A4E, CD2AP, EPHA1, and CD33) on memory independent from APOE in nondemented people 5,6. What is more, patients with APOE ε4 often show some defects in the repair of nerve injury7 as well as exhibit an altered lifespan trajectory in the ability of the brain to dynamically modulate function to cognitive challenge.8…”
Section: Introductionmentioning
confidence: 99%